Penerapan Pencatatan Akuntansi Persediaan Barang Dagang Berdasarkan PSAK No.14 Pada Toko Online Shop CUTIESTORE.CO - Cindy Permata Dewi, Cornelia (CV. Lafadz Jaya, 2022)
The goal of this study was to assess whether the Cutiestore.co Online Shop's inventory and valuation methods were compatible with the PSAK No. 14 statement of financial accounting standards. Documentation, Observation, Interview, and Literature Study are the methods utilized to gather data. Quantitative data analysis is performed by collecting (collecting), reducing (reducing), and displaying (displaying) data (data presentation). The Online Shop uses the FIFO valuation approach and the perpetual recording method for inventory value and recording. In-depth interviews with Cutiestore.co's owner yielded data in the form of an overview of the online store, which was then written up as a report on the findings. After conducting a study, experts assessed that the Cutiestore.co Online Shop's inventory recording, and valuation system complied with PSAK No. 14.